The impact of FADS genetic variants on ω6 polyunsaturated fatty acid metabolism in African Americans - Mathias, Rasika A; Sergeant, Susan; Ruczinski, Ingo; Torgerson, Dara G; Hugenschmidt, Christina E; Kubala, Meghan; Vaidya, Dhananjay; Suktitipat, Bhoom; Ziegler, Julie T; Ivester, Priscilla; Case, Douglas; Yanek, Lisa R; et al. (BMC genetics, 2011)
Background Arachidonic acid (AA) is a long-chain omega-6 polyunsaturated fatty acid (PUFA) synthesized from the precursor dihomo-gamma-linolenic acid (DGLA) that plays a vital role in immunity and inflammation. Variants in the Fatty Acid Desaturase ( FADS ) family of genes on chromosome 11q have been shown to play a role in PUFA metabolism in populations of European and Asian ancestry; no work has been done in populations of African ancestry to date. Results In this study, we report that African Americans have significantly higher circulating levels of plasma AA (p = 1.35 × 10 -48 ) and lower DGLA levels (p = 9.80 × 10 -11 ) than European Americans. Tests for association in N = 329 individuals across 80 nucleotide polymorphisms (SNPs) in the Fatty Acid Desaturase ( FADS ) locus revealed significant association with AA, DGLA and the AA/DGLA ratio, a measure of enzymatic efficiency, in both racial groups (peak signal p = 2.85 × 10 -16 in African Americans, 2.68 × 10 -23 in European Americans). Ancestry-related differences were observed at an upstream marker previously associated with AA levels (rs174537), wherein, 79-82% of African Americans carry two copies of the G allele compared to only 42-45% of European Americans. Importantly, the allelic effect of the G allele, which is associated with enhanced conversion of DGLA to AA, on enzymatic efficiency was similar in both groups. Conclusions We conclude that the impact of FADS genetic variants on PUFA metabolism, specifically AA levels, is likely more pronounced in African Americans due to the larger proportion of individuals carrying the genotype associated with increased FADS1 enzymatic conversion of DGLA to AA.